2019
DOI: 10.1007/s40256-019-00379-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Efficacy of Ezetimibe in Patients with Atherosclerotic Cardiovascular Disease: A Systematic Review and Meta-Analyses

Abstract: Introduction Patients with atherosclerotic cardiovascular disease (ASCVD), especially those with recent (< 1 year) acute coronary syndrome (ACS), are at high risk for recurrent cardiovascular events. This risk can be reduced by lowering lowdensity lipoprotein cholesterol (LDL-C) levels. A comprehensive meta-analysis on the LDL-C-lowering efficacy of ezetimibe is lacking. This study attempts to address this gap. Methods A systematic literature review of randomized controlled trials evaluating the LDL-C-lowering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Meta‐analysis of 12 studies of patients with atherosclerotic cardiovascular disease by Shaya et al summarized that combination therapy with statin and ezetimibe provided an additional LDL‐C reduction versus monotherapy with a statin (mean difference, − 21.86 mg/dL; P <0.0001) after 6 months of treatment. 25 The same beneficial effect was observed in patients with recent ACS, with mean treatment difference of −19.19 mg/dL (95% CI, −25.22 to −13.16 mg/dL; P <0.0001). 25 In the meta‐analysis by Zhan et al, including 23 499 patients (26 randomized controlled trials), the authors showed a 6% (0.94 [95% CI, 0.90–0.98]) significant reduction of major adverse events with the combination therapy compared with statin monotherapy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Meta‐analysis of 12 studies of patients with atherosclerotic cardiovascular disease by Shaya et al summarized that combination therapy with statin and ezetimibe provided an additional LDL‐C reduction versus monotherapy with a statin (mean difference, − 21.86 mg/dL; P <0.0001) after 6 months of treatment. 25 The same beneficial effect was observed in patients with recent ACS, with mean treatment difference of −19.19 mg/dL (95% CI, −25.22 to −13.16 mg/dL; P <0.0001). 25 In the meta‐analysis by Zhan et al, including 23 499 patients (26 randomized controlled trials), the authors showed a 6% (0.94 [95% CI, 0.90–0.98]) significant reduction of major adverse events with the combination therapy compared with statin monotherapy.…”
Section: Discussionmentioning
confidence: 62%
“… 25 The same beneficial effect was observed in patients with recent ACS, with mean treatment difference of −19.19 mg/dL (95% CI, −25.22 to −13.16 mg/dL; P <0.0001). 25 In the meta‐analysis by Zhan et al, including 23 499 patients (26 randomized controlled trials), the authors showed a 6% (0.94 [95% CI, 0.90–0.98]) significant reduction of major adverse events with the combination therapy compared with statin monotherapy. 26 They also showed that adding ezetimibe to statins reduced the risk of nonfatal myocardial infarction (risk ratio [RR], 0.88 [95% CI, 0.81–0.95]) and nonfatal stroke (RR, 0.83 [95% CI, 0.71–0.97]).…”
Section: Discussionmentioning
confidence: 62%
“…Conversely, the prescription of an anti-PCSK9 mAb was very infrequent, even in Group III (0.1%). Given that these treatments have been shown in meta-analyses to provide more robust reductions in LDL-C than statins alone 28,29) , as well as benefits in terms of cardiovascular outcomes 28,30,31) , the fact that they are not more widely used in patients failing to meet LDL-C goals on intensive statin monotherapy may represent a loss of treatment opportunity for these patients. In this study, although more patients who were prescribed combination therapy with a statin and either ezetimibe or an anti-PCSK9 mAb (or both) achieved their LDL-C goals than did patients receiving statin monotherapy, the proportion of patients receiving such a combination therapy was <10%, principally in recorded in the MDV database, and the use of a standardized coding system for documenting the study variables.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in LDL cholesterol levels was almost 22% higher when ezetimibe was combined with rosuvastatin 40 mg than when the statin alone was given, with 32 and 31% increases also being observed after ezetimibe was added to atorvastatin 80 mg or simvastatin 40 mg, respectively. A recent meta-analysis including 12 studies [25] found that the ezetimibe plus statin combination achieved a greater absolute LDL cholesterol reduction than statin monotherapy, with a mean difference of 21.86 mg/dL (95% CI 26.56 to 17.17; p < 0.0001) after 6 months of treatment. These results being consistent with the 19-23% LDL cholesterol reduction previously described for ezetimibe when added to statin therapy [26,27].…”
Section: Discussionmentioning
confidence: 99%